(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
The article emphasizes the efficiency of using interactive methods in teaching. Interactive learning is an important condition and result of an integrated approach in training. For effective organization of the process of teaching in the real situation of the educational practice teacher needs a deep understanding of psychological content of lesson.